Corruption, Structural Reforms, and Economic Performance in the Transition Economies - Abed, George (IMF Working Papers; Working Paper ;, 2000)
Recent studies have highlighted the adverse impact of corruption on economic performance. This paper advances the hypothesis that corruption is largely a symptom of underlying weaknesses in public policies and institutions, a formulation that provides deeper insights into economic performance than do measures of 'perceived corruption.' The hypothesis is tested by assessing the relative importance of structural reforms vs. corruption in explaining macroeconomic performance in the transition economies. The paper finds that for four widely used measures of economic performance-growth, inflation, the fiscal balance, and foreign direct investment-structural reforms tend to dominate the corruption variable.